2016
DOI: 10.1111/tbed.12548
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Serotypes A and Asia-1 Foot-and-mouth Disease Viruses in Balochistan, Pakistan, in 2011

Abstract: This study reports characterization of foot-and-mouth disease virus (FMDV) in samples collected from Balochistan, Pakistan. FMDV was detected by pan-FMDV real-time RT-PCR in 31 samples (epithelial and oral swabs) collected in 2011 from clinical suspect cases. Of these, 29 samples were serotyped by serotype-specific real-time RT-PCR assays and were confirmed by sequencing the VP1 coding region. Sixteen samples were found positive for serotype A and eight for serotype Asia-1, whereas five samples were found posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 31 publications
4
23
0
Order By: Relevance
“…The simultaneous detection of two strains of FMDV in a single clinical field sample has been reported previously in a small number of samples collected in endemic countries, including Pakistan (Jamal et al., ; Ullah et al., ), Nigeria (Wungak et al., ) and Vietnam (Lee et al., ). However, the presence of two viruses does not differentiate coinfection in vivo from artifactual codetection associated with cross‐contamination of samples on the farm, during collection or in the laboratory.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…The simultaneous detection of two strains of FMDV in a single clinical field sample has been reported previously in a small number of samples collected in endemic countries, including Pakistan (Jamal et al., ; Ullah et al., ), Nigeria (Wungak et al., ) and Vietnam (Lee et al., ). However, the presence of two viruses does not differentiate coinfection in vivo from artifactual codetection associated with cross‐contamination of samples on the farm, during collection or in the laboratory.…”
Section: Discussionmentioning
confidence: 66%
“…Ullah et al. () found poor sensitivity of an Ag‐ELISA compared to VP1 sequencing of raw samples, which the authors suggested was due to poor sample quality or low viral load in some samples. Whilst Ag‐ELISA performance is affected by sample quality and viral load in the sample, virus isolation prior to Ag‐ELISA or VP1 sequencing ensured the presence of intact virus in the tested samples in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular and serological surveys in livestock have shown that FMDV has been endemic in Iran for more than 60 years [24]. In the last 20 years the most frequent FMDV isolate has been serotype A but serotype O and Asia 1 have been reported from major outbreaks in Iran and neighbouring countries [25, 26]. Serotypes O and A were responsible for recent outbreaks in 2014 and 2015 [27, 28].…”
Section: Introductionmentioning
confidence: 99%